SARS-CoV-2 infecção e replicação: estudo da flexibilização conformacional por métodos de simulação molecular e química quântica - Mendonça, José Gutembergue de (2024)
The emergence of the novel SARS-CoV-2 coronavirus, which has caused the ongoing global pandemic of coronavirus disease 2019 (Covid-19), has had an unparalleled impact on the lives of all humans. In this regard, proteases that are responsible for viral replication and infection, as well as mutant strains, have been a subject of concern for scientists, who are engaged in efforts to comprehend the conformational behavior of these proteases. It has been demonstrated that the zinc finger domain plays a pivotal role in the structural integrity of the Papain-Like Protease (PLpro) protein, exerting an influence on the conformational behavior of the ubiquitin-like domain. Moreover, mutations in the receptor-binding domain (RBD) have been observed to enhance the resistance of the virus to neutralizing antibodies and the affinity for the receptor. In this study, molecular dynamics simulations and quantum descriptor calculations were employed to elucidate potential inter-domain conformational variations and the reactivity of PLpro. Moreover, these methods were employed to assess the conformational variations of the RBD and its mutants, which were categorized based on their affinity for the receptor and resistance to antibodies. The results indicate that the Zn2+ cation, which is tetracoordinated with the cysteines in the PLpro structure, serves to stabilize the zinc finger region, thereby increasing the mobility and reactivity of the ubiquitin domain, particularly in the context of SARS-CoV-2. This indicates that this region exerts an influence on the binding conformations to the post-translational substrates of ubiquitin and ISG15, which are components of the antiviral immune response. The clustering of molecular dynamics trajectories enabled the extraction of the most populated structures within the conformational space of each system. The results for the RBD responsible for receptor binding demonstrated an increase in the fluctuation of residues 360-374 and in the receptor binding motif (RBM). It was observed that in the RBM region, there was a greater standard deviation for the mutations that exhibited reduced interaction with the receptor and increased resistance to antibodies. This phenomenon may be related to a greater conformational range and lower reactivity of these mutations, which may represent a strategy to evade the host’s immune response. The results obtained in this study may contribute to a greater understanding of the behavior and conformational patterns of two proteins involved in different stages of the viral life cycle: The PLpro responsible for infection and the spike protein, which is responsible for invading the host cell.